Zastosowanie wybranych metod klasyfikacji do rozpoznawania indywidualnych kredytobiorców - Chrzanowska, Mariola; Witkowska, Dorota (Application of Selected Methods to the Individual Borrowers Recognition, 2007)
In the paper the results of application selected methods to the individual credit repayment are presented. These methods are: binary regression, Bayesian discriminant analysis and aggregated classification trees. The experiments are provided for actual data concerning 2547 borrowers. The training set contains 560 selected objects and testing set - 278 cases. The efficiency of employed methods is evaluated in terms of chosen measures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 108-114